"Kenali Dirimu, Kelola Emosimu" Pelatihan Regulasi Emosi untuk Meningkatkan Kesejahteraan Psikologis Mahasiswa - Raihan Saputra; Ririn Ida Royani; Selly Dwining Maulidina; Rivandy Ilham Akbar; Arfian Arfian (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
College students face various academic, social, and adult transition pressures that can affect their psychological condition. Emotional regulation is a crucial skill to balance affective responses to stress. This service aims to improve the ability of student participants to regulate emotions to improve their psychological well-being. This activity began with observation to select participants who fit our research criteria, continued with the preparation of an easy-to-understand training module, and ended with socialization and training for student participants. The training was held on June 4, 2025 at the Bhayangkara University Campus, Jakarta Raya Room 403, Bekasi, West Java. The training evaluation showed an increase in participants' understanding in regulating their psychological well-being emotions. The positive impact of this program is that emotional regulation training helps create a more stable and healthy mental condition, which has a direct impact on improving the quality of life and learning achievement of students.